All-inorganic CsPbBr3 perovskite solar cells with enhanced efficiency by exploiting lone pair electrons via passivation of crystal boundary using carbon nitride (g-C3N4) nanosheets. (September 2021) - Liu, W.-W.; Liu, Y.-C.; Cui, C.-Y.; Niu, S.-T.; Niu, W.-J.; Liu, M.-C.; Liu, M.-J.; Gu, B.; Zhang, L.-Y.; Zhao, K.; Ran, F.; Chueh, Y.-L.
Abstract: Fast extraction of photo-generated charge plays a crucial function in improving the photovoltaic conversion efficiency (PCE) of the perovskite solar cells (PSCs). Here, an effective strategy to decrease the charge recombination losses by introducing versatile carbon nitride ( g -C3 N4 ) nanosheets to the CsPbBr3 films was demonstrated. The incorporation of the g -C3 N4 additive can restrain the nucleation and crystalline growth rate of perovskite films by an interaction of lone pair electrons from the exposed N atoms to the PbBr2 precursor, resulting in high-quality CsPbBr3 films with an increase in crystalline size. Notably, a 'coupling effect' between the lone pair electrons from g -C3 N4 nanosheets and unsaturated Pb dangling bonds (Br vacancies) around the grain boundaries significantly decreases trap states caused by defects, leading to the fewer recombination centers in CsPbBr3 films. The g -C3 N4 nanosheets serving as an energy barrier can also successfully suppress the recombination loss of back electrons with holes from the g -C3 N4 interface, yielding a superior PCE of 8.0% with a fill factor of 80.25%. The result opens an alternative path to enhance the performance of CsPbBr3 PSCs by passivating the trap states of perovskite films with the improvement of the crystallization quality and charge extraction efficiency. Graphical abstract: Fast extraction of photo-generated charge plays a crucial function in improving the photovoltaic conversion efficiency (PCE) of the perovskite solar cells (PSCs). Here, an effective strategy to decrease the charge recombination losses by introducing versatile carbon nitride ( g -C3 N4 ) nanosheets to the CsPbBr3 films was demonstrated, yielding an excellent PCE of 8.00% with a fill factor of 80.25%. Image 1 Highlights: The g -C3 N4 additive can restrain the nucleation and crystalline growth rate of perovskite films by an interaction of lone pair electrons from the exposed N atoms to the PbBr2 precursor, resulting in high-quality CsPbBr3 films with an increase in crystalline size and decreased derivative phases from CsPb2 Br5 . The coupling effect between the lone pair electrons from g -C3 N4 nanosheets and unsaturated Pb dangling bonds (Br vacancies) around the grain boundaries significantly decreases trap states, leading to fewer recombination centers in CsPbBr3 films. The conduction band (CB) energy level of g -C3 N4 nanosheets serving as an energy barrier can effectively suppress the recombination losses between back electrons and holes from the interface of CsPbBr3 /carbon.